Kje si dijaki izposojajo knjige za domače branje in kako - Švab, Katarina (Šolska knjižnica, 2012)
the paper presents results of a survey of book searching for the purpose of home reading. The study surveyed students of two Slovenian grammar schools. We were interested to see if library catalogue was used and in which type of library (school or public) they borrow the books. The trend of low loans of books for home reading in secondary school libraries is equal to the trend in primary school libraries, although secondary school libraries hold larger numbers of home reading books that public libraries. Information technology equipment in secondary school libraries is good (one quarter offers more than 4 computers for the users). Results of interviews have shown that students more often use library catalogue if the librarian teaches the course Library and information knowledge. However, the use of catalogue to search for known materials is generally rather low (32%), because the libraries offer separate shelves for home reading books. Such arrangement makes searching easire, but on the other hav+nd does not enable the user to see other versions of the work.
Keywords: domače branje; knjižnični katalogi; knjižnično informacijsko znanje; srednje šole; šolske knjižnice